Composite functional material for accelerating granulation of aerobic sludge as well as preparation method and application of composite functional material

Through the composite functional materials and grading control strategies of core-shell structure, the problems of long aerobic granular sludge aerobic granular sludge accumulation cycle and low nitrogen removal efficiency are solved, and efficient and low-carbon sewage treatment is achieved, avoiding microplastic pollution and material loss.

CN120328731APending Publication Date: 2025-07-18GUANGXI BOSSCO ENVIRONMENTAL PROTECTION TECH CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510666270.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-22
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

In the prior art, aerobic granular sludge has a long acclimation cycle and high drug dosing costs, and it is difficult to coordinate nitrogen removal and granulation, and the risk of microplastic pollution caused by defects in sulfur autotrophic denitrification materials and single carrier function, obstacles in mass transfer interfaces and poor mechanical strength of the material.

Method used

The core-shell structure composite functional materials are adopted, the core layer contains sulfur source, conductive dielectric and pH buffering agent, and the shell layer contains polylactic acid, extracellular polymer inducer and pyrote. The porous skeleton is formed through low-temperature foaming and plasma etching. Combined with a low-dissolved oxygen environment controlled by grading, it realizes autotrophic-heterotrophic synchronous nitrification denitrification and sulfur source sustained release.

Benefits of technology

The sludge granulation cycle is shortened, the nitrogen removal efficiency is improved, the material is completely biodegraded, microplastic pollution is avoided, mass transfer efficiency and bacterial enrichment ability are improved, and operating costs and energy consumption are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120328731A_ABST
    Figure CN120328731A_ABST
Patent Text Reader

Abstract

The invention discloses a composite functional material for accelerating granulation of aerobic sludge. The composite functional material is of a core-shell structure, in the core-shell structure, a core layer comprises the following raw materials in percentage by mass: 30-50% of a sulfur source, 5-10% of a conducting medium and 0-5% of a pH buffering agent; the shell layer is prepared from the following raw materials in percentage by mass: 10 to 50 percent of polylactic acid, 0.6 to 1 percent of extracellular polymeric substance induction enhancer A, 0.002 to 0.005 percent of extracellular polymeric substance induction enhancer B and 15 to 35 percent of pyrite; the use amount of the chitin matrix is 50-60% of the mass of the core layer, and the chitin matrix is used as a raw material component of the core layer and the shell layer at the same time. The invention also discloses a preparation method and an application method of the compound. According to the method, dominant bacteria can be rapidly enriched, the sludge granulation period is remarkably shortened, the denitrification efficiency is improved, and the method has the advantage of environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sewage treatment, and particularly relates to a composite functional material for accelerating aerobic sludge granulation, a preparation method thereof, and an application thereof. Background Art

[0002] In the field of sewage treatment, aerobic granular sludge exhibits significant advantages compared with traditional flocculent sludge. Flocculent sludge has a loose structure (particle size 0.05 - 0.2 mm), poor settling performance (2 - 10 m / h), is prone to sludge bulking, and requires multiple processes to achieve nitrogen and phosphorus removal. Aerobic granular sludge is formed by the self-aggregation of microorganisms into a dense spherical structure (diameter 0.5 - 3 mm, settling velocity 15 - 50 m / h). Its stratification characteristics (outer aerobic / inner anoxic-anaerobic) support the simultaneous removal of COD (>95%), nitrogen (TN > 80%), and phosphorus (PAOs > 30%) in a single reactor. At the same time, the biomass concentration (MLSS 8 - 15 g / L), the ability to resist load shocks (±50% COD fluctuation), and the advantages in terms of land occupation and energy consumption (volume load increased by 3 - 5 times, aeration energy consumption reduced by 15 - 30%) are significantly better than traditional processes, meeting the requirements of sewage treatment intensification and low carbonization.

[0003] Currently, the rapid domestication of aerobic granular sludge mainly relies on methods such as substrate regulation (optimization of C / N / P gradients), hydraulic selection pressure (settling time < 5 min), and pulsed aeration (dynamic switching of DO), but still faces bottlenecks such as a long startup period (1 - 3 months), granule disintegration under high organic load (>5 kg COD / m 3 ·d), and fluctuations in nitrogen and phosphorus removal efficiency caused by substrate competition between denitrifying bacteria and phosphorus-accumulating organisms (PAOs), restricting its engineering application. The rapid granulation of aerobic microorganisms is the core to break through the above limitations. By accelerating the enrichment of functional microbial communities and the stability of physical structures, it can significantly shorten the system startup period and improve the co-removal efficiency of pollutants.

[0004] In recent years, the autotrophic denitrification technology based on sulfur has become a research hotspot under the background of "dual carbon" due to its characteristics such as no need for organic carbon sources, low sludge yield, and low carbon emissions. Sulfur autotrophic denitrification uses reduced sulfur (S2-, S, S2O32-, etc.) as the electron donor and inorganic carbon as the carbon source to reduce nitrate to nitrogen, and the denitrification efficiency can reach more than 90%. Coupling sulfur autotrophic denitrification with aerobic granular sludge technology can use the sulfur oxidation products to strengthen the stability of the granule structure. At the same time, the metabolic pathway driven by sulfide can directionally enrich dominant strains, forming a granulation microenvironment with "autotrophic-heterotrophic" synergy, thereby accelerating the aggregation and functionalization of aerobic microorganisms. This synergistic system can not only shorten the domestication period of aerobic granular sludge but also reduce the dependence on organic carbon sources for traditional heterotrophic denitrification, providing an innovative direction for constructing efficient and low-carbon sewage treatment technologies.

[0005] Chitin is a raw material that is easily available in coastal aquaculture processing plants and the like. Chitin contains chitosan (20 - 30%), calcium carbonate (30 - 50%), protein (20 - 40%) and a small amount of lipids. Chitosan, with the chemical name of β-(1,4)-2-acetamido-2-deoxy-D-glucopyranose, is the second most abundant natural polysaccharide in nature after cellulose. It has higher reactivity and solubility. If chitosan is extracted, it can be prepared into a porous sponge material that is easily biodegradable and has high green environmental protection advantages. Therefore, the development of chitosan functional materials has great potential.

[0006] Patent No. CN 114620832 A, "A Sulfur-Based Autotrophic Microbial Denitrification Material and Its Preparation and Application Method", mixes a sulfur-containing raw material and lime powder evenly to obtain a mixed material; adds it to a molding machine and heats it to a viscous and plastic flow state; extrudes, cuts and cools the material to obtain spherical or rod-shaped particles with a diameter of 250 mm. The prepared material is a solid rigid material, not wear-resistant, with a large material loss, and a low denitrification efficiency.

[0007] Patent No. CN118878074A, "A Method for Preparing Sulfur-Iron-Based Autotrophic Denitrification Filler by Mechanochemical Method and Its Application", mentions a sulfur-iron-based autotrophic denitrification filler. It grinds elemental sulfur powder, divalent iron source and activated carbon powder into a powder state and then heats and melts them. Immediately afterwards, granulates, cools and crushes them to obtain the sulfur-iron-based autotrophic denitrification filler. Although it has a high denitrification rate, it also has defects such as easy consumption, and the problem of suspension stability of the material has not been solved. In addition, there is no foaming process in the preparation process of the above two patent materials, and the porosity of the materials is low, which is not conducive to mass transfer and the attachment of dominant bacteria.

[0008] In a Chinese invention patent (Publication No.: CN 16332329 A), a slow-release sulfur autotrophic denitrification biological filter material and its preparation method and application are disclosed. It uses a special adhesive and adds it to the core material balls made of specific ingredients mainly composed of sulfur, and uses a specific autoclaved concrete premix as the aggregate, and obtains the biological filter material through static maintenance and curing, thus realizing the slow-release effect of the sulfur source and the ability to supplement the carbon source.

[0009] In a Chinese invention patent (Publication No.: CN 118108346 A), a composite filler for a sulfur autotrophic denitrification biological filter and its preparation method and application are disclosed. This scheme uses polystyrene microspheres as the carrier skeleton, loads ferrous sulfide and elemental sulfur nanoparticles, and enhances the attachment of microorganisms through triethylamine groups. The carrier has a high porosity and is conducive to the enrichment of dominant bacteria, but the material skeleton is non-degradable, resulting in microplastic pollution due to long-term retention.

[0010] A porous material based on β-chitin, its preparation method and application are disclosed in a Chinese invention patent (application number: 202311471673.0). It has high organic matter adsorption, hydrophilicity, underwater resilience and solubility. During preparation, it does not require a large amount of chemical reagents and has low energy consumption. It is suitable for the field of environmental water treatment and is an environmentally friendly and degradable advantageous material. However, the function of the material carrier is single.

[0011] Therefore, the following existing technical bottlenecks need to be solved urgently:

[0012] 1. The acclimation period of aerobic granular sludge is long and the chemical addition cost is high: Traditional aerobic granular sludge relies on the spontaneous aggregation of microorganisms. It generally takes 1 - 3 months to form a stable granular sludge structure, and it is easily damaged by hydraulic shear; during the acclimation process, it is usually necessary to use an external carbon source to achieve high-concentration organic matter to maintain the structural stability of aerobic granular sludge, resulting in high chemical addition costs.

[0013] 2. It is difficult to coordinate denitrification and granulation: Heterotrophic denitrification and aerobic granulation will compete for carbon sources simultaneously, and the denitrification process hinders the granulation of aerobic sludge; in addition, although sulfur autotrophic denitrification does not require an external carbon source, due to the oxidation by-products of sulfur, such as sulfate ions and hydrogen ions, to a certain extent, they will inhibit the microbial activity, resulting in the disintegration of granules. Therefore, it is difficult to coordinate and couple denitrification and granulation.

[0014] 3. Defects in sulfur autotrophic denitrification materials and out-of-control sulfur release: In conventional sulfur autotrophic denitrification technology, the sulfur source release rate is uncontrollable, the autotrophic denitrification effect is poor, the mechanical strength of the material is poor, and the raw material loss rate is high: A high dissolved oxygen environment will cause the loss of the sulfur source due to abiotic oxidation; the sulfur source has a small specific surface area and low porosity, which will lead to the obstruction of the mass transfer interface of the sulfur source and slow sulfur source release, being unfavorable for the enrichment of dominant strains and having a low biological load, resulting in poor denitrification effect; conventional sulfur source particles do not have a solid and wear-resistant filler skeleton, and the mechanical strength is poor. Under the action of gravity, the material layer structure is easily broken or flattened; during use, due to being gradually consumed, the mass of the sulfur source becomes smaller and it is easily lost with hydraulic scouring.

[0015] 4. The carrier function is single and there are non-degradable materials, resulting in a risk of microplastic pollution: The commonly used material carriers on the market have a single function and cannot simultaneously provide microbial attachment points, electron donors, and extracellular polymer inducer induction factors, resulting in low efficiency of aerobic sludge granulation, insufficient microbial directional enrichment and co-regulation; moreover, the commonly used carrier fillers on the market are petroleum-based plastic skeletons (such as polyethylene, polyurethane, etc.). If they remain in the system for a long time, they will cause microplastic pollution.

[0016] To solve the above problems, it is urgent to find a broad-spectrum, easily available, green and environmentally friendly biodegradable material that can simultaneously achieve autotrophic-heterotrophic simultaneous nitrification and denitrification, sulfur slow release, pH self-balance, and efficient secretion of extracellular polymer inducers, so as to rapidly enhance aerobic microbial granulation, shorten the system startup time, improve the treatment efficiency, break through the bottleneck of traditional biological treatment by accelerating the enrichment and structural stability of functional flora, provide the core driving force for efficient and low-carbon sewage treatment, and have environmental protection advantages. Summary of the Invention

[0017] The purpose of the present invention is to provide a composite functional material for accelerating aerobic sludge granulation, a preparation method thereof, and an application thereof to solve the technical problems raised in the above background technology.

[0018] To achieve the above purpose, the present invention adopts the following technical solutions:

[0019] A composite functional material for accelerating aerobic sludge granulation, the composite functional material having a core-shell structure; in the core-shell structure, the core layer comprises raw materials in the following mass percentages: 30-50% of a sulfur source, 5-10% of a conductive medium, and 0-5% of a pH buffer; the shell layer comprises raw materials in the following mass percentages: 10-50% of polylactic acid, 0.6-1% of extracellular polymer induction enhancer A, 0.002-0.005% of extracellular polymer induction enhancer B, and 15-35% of pyrite; it further includes a chitin matrix, with a dosage of 50-60% of the mass of the core layer, and the chitin matrix serves as a raw material component of both the core layer and the shell layer.

[0020] Further, the sulfur source is one or both of pyrite and elemental sulfur.

[0021] Further, the conductive medium is one or both of nano-carbon powder and graphite.

[0022] Further, the pH buffer is nano-sodium silicate or nano-calcium carbonate.

[0023] Further, the extracellular polymer induction enhancer A is humus.

[0024] Further, the extracellular polymer induction enhancer B is AI-2 signaling molecule.

[0025] A preparation method of a composite functional material for accelerating aerobic sludge granulation, comprising the following steps:

[0026] S1 Pretreatment of chitin: The chitin is washed with clean water, dried, mechanically crushed and screened into nano-chitin powder. Then the chitin powder is dissolved in 1% NaOH lye in small amounts and multiple times for deproteinization, while stirring continuously. The stirring speed is maintained at 700 - 900 r / min, the temperature is controlled at 55 - 60 °C, and stirring is carried out for 2 - 3 h. The endogenous calcium carbonate is retained, and finally it is vacuum dried for standby to obtain the chitin matrix;

[0027] S2 Preparation of the core layer and freeze forming: The sulfur source, chitin matrix, and conductive medium are mixed at a mass ratio of 5:4:1. Meanwhile, the content of endogenous calcium carbonate in the chitin matrix is detected, and a pH buffer is added according to the content of endogenous calcium carbonate. After mixing, it is dispersed in the chitin solution and homogenized by ultrasonic waves for 30 - 60 min. After good homogenization, it is preformed into spherical particles with a diameter of 1 - 2 mm by dropping and freezing with liquid nitrogen, and then the spherical particles are vacuum freeze-dried at -50 °C for 24 h. After freezing, it is cross-linked with 1% glutaraldehyde vapor for 2 h, and after cross-linking, it is coated with silica to a thickness of 1 - 2 μm to obtain the core layer microspheres;

[0028] S3 Preparation of the shell layer and low-temperature foaming: The core layer microspheres and polylactic acid particles are melt-blended at a volume ratio of 1:1 at a temperature of 85 - 95 °C, and then foamed with supercritical CO2. The foaming pressure is 15 MPa and the temperature is 80 °C, so that the polylactic acid particles are foamed to coat the core layer to form particles;

[0029] S4 Functional loading and surface modification: The particles obtained in S3 are immersed in an ethanol mixed solution of humic acid and AI-2 for 30 - 60 min. The coating thickness is controlled to be 5 - 10 μm by adjusting the concentration of the mixed solution. Through loading within the pores of the shell layer, vacuum drying, and plasma etching the surface at a power of 50 W for 6 - 10 min, the surface roughness Ra is adjusted to 1.8 - 2.8 μm to form a micron-scale rough structure, obtaining the preformed material;

[0030] S5 Density regulation and stability enhancement: The density of the preformed material is adjusted to 0.95 - 1.05 g / cm3 by spraying a pyrite suspension, and heat treatment is carried out in a nitrogen atmosphere to finally obtain the particle size composite functional material.

[0031] Furthermore, in S2, if the mass ratio of the endogenous calcium carbonate content in the chitin matrix to the sulfur source is less than 1:1, a pH buffer is added to make up the deficiency.

[0032] Furthermore, the application of the composite functional material in the treatment of low carbon-nitrogen ratio wastewater in municipal, industrial, surface water, groundwater, and aquaculture water.

[0033] Application of the composite functional material for accelerating aerobic sludge granulation, and the application method of the composite functional material includes the following steps:

[0034] S1: Material dosing and reactor startup: Add the composite functional material carrier at 10 - 20% of the reactor volume, control the initial dissolved oxygen at 0.5 - 1.0 mg / L, pH = 6.5 - 7.5, and HRT = 4 - 12 h;

[0035] S2: Low dissolved oxygen hierarchical control:

[0036] Phase I, days 0 - 7, enrichment of sulfur autotrophic bacteria: DO = 0.5 - 1.0 mg / L, influent flow rate 10 - 30%;

[0037] Phase II, days 8 - 14, granulation induction: Increase DO = 1.0 - 2.0 mg / L, influent flow rate 30 - 70%;

[0038] Phase III, > 14 days, stable operation: Maintain DO = 2.0 - 3.0 mg / L, influent flow rate 70 - 100%;

[0039] S3: Long - term maintenance and material degradation: After the domestication of aerobic granular sludge, the process operates stably.

[0040] The principle of the composite functional material of the present invention is:

[0041] The core layer serves as the core of sulfur autotrophic function, and the shell layer serves as the granulation induction layer. Autotrophic denitrification occurs inside the core, and heterotrophic nitrification occurs outside the shell. Large - particle sulfur sources are intercepted by the small - pore - diameter porous network shell layer, realizing sulfur source slow release and efficient nitrogen removal through simultaneous autotrophic - heterotrophic nitrification - denitrification.

[0042] The principles of the raw materials of the present invention are as follows:

[0043] Sulfur source: As the electron donor for sulfur autotrophic denitrification, it provides electrons through oxidation reactions, driving denitrifying bacteria to reduce nitrate to nitrogen for nitrogen removal.

[0044] Conductive medium: Forms a transmembrane electron transfer network, promotes electron transfer between sulfur autotrophic bacteria and aerobic bacteria, improves the denitrification rate, shortens the reaction time, and enhances the microbial synergy.

[0045] pH buffer: Supplies alkalinity to ensure the efficient progress of sulfur autotrophic denitrification in a neutral environment and avoid acid inhibition of microbial activity.

[0046] Polylactic acid: Forms a porous framework with the chitin matrix, has a significant specific surface area, strengthens the microbial attachment ability, and can be completely biodegradable to avoid pollution.

[0047] Humic substances, AI - 2 signaling molecules: Humic acid stimulates the secretion of extracellular hydrophobic polymeric proteins by microorganisms through hydrophobic interactions. At the same time, the AI - 2 signaling molecule activates the quorum sensing pathway, shortens the microbial formation cycle, and accelerates sludge granulation.

[0048] Pyrite: Adjust the density to achieve the suspension-sedimentation balance of the material in water, so as to improve the microbial interception rate.

[0049] Chitin matrix: Derived from the chitin of crustacean organisms remaining in coastal seafood processing plants and other places, such as shrimps, crabs, shellfish, etc.; in the core layer, the chitin matrix has a porous network structure, and three-dimensional interconnected pores are formed through freeze-drying, so that large-particle sulfur sources are physically intercepted by the small-aperture chitin network, thereby realizing the slow release of sulfur sources; in the shell layer, the chitin matrix and polylactic acid form a porous skeleton, which promotes the attachment of microorganisms and can be completely biodegradable at the same time, avoiding pollution.

[0050] The principle of the preparation method of the present invention is as follows:

[0051] S1: Use strong alkali to break the peptide bonds in protein molecules, hydrolyze them into soluble amino acids or short peptides and remove them, and retain endogenous calcium carbonate as an endogenous pH buffer to obtain a chitin matrix containing chitin and endogenous calcium carbonate.

[0052] S2: Disperse the sulfur source, chitin powder, and conductive medium in the chitin solution. NaOH in the chitin solution breaks the hydrogen bonds of chitin, and urea is used as a dispersant to prevent re-aggregation; ultrasonic homogenization can improve the dispersion effect; liquid nitrogen droplet freezing can instantaneously freeze and lock the uniform dispersion state of the sulfur source, conductive medium, and chitin to form regular spheres; through glutaraldehyde cross-linking treatment, the compressive strength > 5N can be obtained to prevent the core layer from swelling or disintegrating in a humid environment; through silica coating, the heat resistance of the core layer can be enhanced to prevent the subsequent high-temperature operation from affecting the core layer.

[0053] S3: After the polylactic acid and the core layer microspheres are melt-blended, supercritical CO2 foaming technology is used for foaming treatment. CO2 has gas diffusivity and liquid solubility in the supercritical state of 15MPa and 80°C, and penetrates into the polylactic acid melt, so that the polylactic acid and part of the chitin powder in the core layer microspheres jointly form a chitin-polylactic acid composite foamed porous skeleton, thereby forming a porous shell layer with a bubble pore size of 50-200 mesh, a porosity > 70%, and a particle size of 2.0-3.0mm to coat the core layer.

[0054] S4: The ethanol solution (polar solvent) of humic acid and AI-2 penetrates into the pores of the shell layer through capillary action and is fixed in the pores after vacuum drying; the surface of the material is bombarded with high-energy plasma to etch micron-sized pits, thereby forming a micron-sized rough structure, enhancing the surface roughness and hydrophilicity, and increasing the microbial attachment ability.

[0055] S5: By spraying the pyrite suspension, adjust the density of the material to achieve the suspension-sedimentation balance of the material in water, so as to improve the microbial interception rate.

[0056] In the application method of the present invention, the principle of hierarchical control is:

[0057] Phase I: Control DO = 0.5 - 1.0 mg / L to maintain an anoxic condition, where sulfur autotrophic bacteria dominate denitrification, reducing NO3 - gradually to N2 (shortcut denitrification pathway: NO3 - → NO2 - → N2), removing nitrate and generating S 2 or S 0 micro-particles, with a nitrite accumulation rate > 65%; control the influent water volume at 10 - 30%. The lower influent water volume results in a lower hydraulic shear force, protecting the initially attached microbial film and preventing carrier loss.

[0058] Phase II: Control DO = 1.0 - 2.0 mg / L, increase DO, the carrier shell adsorbs aerobic bacteria, and stimulates aerobic bacteria to secrete extracellular polymers, forming a biofilm on the carrier surface; increase the influent water volume by 30 - 70%, making the sludge density tend to be compact and granulate rapidly, with the average daily increase in particle size of 0.1 - 0.2 mm;

[0059] Phase III: Control DO = 2.0 - 3.0 mg / L, further increase DO, enabling the sulfur autotrophic bacteria in the core and the aerobic bacteria in the shell to achieve simultaneous nitrification / denitrification through "sulfur - oxygen" transmembrane transfer, achieving TN removal.

[0060] The beneficial effects of the present invention compared with the prior art are as follows:

[0061] 1. The composite functional material of the present invention has a core - shell structure. The core layer serves as the sulfur autotrophic functional core, and the shell layer serves as the granulation induction layer. Combining the porous degradable skeleton shell material structure to wrap the sulfur source core and functional additives, coupling the material density regulation technology and the low - dissolved - oxygen hierarchical control strategy, simultaneously realizing efficient nitrogen removal by autotrophic - heterotrophic simultaneous nitrification and denitrification, slow release of sulfur source, directional enrichment of microorganisms, PH self - balance, and efficient secretion of extracellular polymers, shortening the sludge granulation period, with a stable sulfur release rate, capable of forming high - density aerobic granular sludge within 14 - 16 days, with the sulfur source utilization rate increased to more than 85% and the TN removal rate > 90%, solving the bottleneck problems such as carbon source dependence, slow granulation, and by - product inhibition in traditional technologies, and having significant economic and environmental benefits.

[0062] 2. In the shell layer structure of the present invention, polylactic acid and chitin powder form a chitin - polylactic acid composite skeleton carrier. Through the synergistic effect of natural chitin and bio - based polylactic acid, the material can be completely biodegradable, avoiding pollution and being green and environmentally friendly.

[0063] 3. The present invention physically limits sulfur through the chitin porous network and combines with the low - temperature foaming process, which can stabilize the sulfur release rate, improve sulfur utilization rate, reduce the generation amount of sulfate, and avoid system acidification from the source,

[0064] 4. The chitin matrix raw material of the present invention is derived from crustaceans. Through alkali pretreatment of crustaceans, proteins are removed and endogenous CaCO₃ is retained, which can continuously neutralize H⁺, stabilize the pH at 7, achieve pH self - balance, reduce the material preparation cost and operating energy consumption, and simultaneously achieve efficient denitrification and economic optimization. + , stabilize the pH at 7, achieve pH self - balance, reduce the material preparation cost and operating energy consumption, and simultaneously achieve efficient denitrification and economic optimization.

[0065] 5. The present invention regulates the material density by loading pyrite to achieve the suspension - sedimentation balance, provides stable attachment sites for the enrichment of core bacteria, ensures the mass transfer efficiency while having a high interception rate, and accelerates the densification of granular sludge.

[0066] 6. The present invention denitrifies wastewater through a hierarchical control method. Through low, medium, and high DO gradients, microorganisms are gradually domesticated to transition from sulfur autotrophic denitrification to simultaneous nitrification - denitrification, shortening the granulation period. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 is a schematic diagram of the core - shell structure of the composite functional material of the present invention;

[0068] Figure 2 is a schematic diagram of the structure of the core layer of the present invention;

[0069] Figure 3 is a scanning electron microscope (SEM) image of the pore channels of the shell layer in Example 1 of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0070] To make the objectives, technical solutions and advantages of the present invention more clearly understood, the following preferred embodiments are cited with reference to the accompanying drawings for further detailed description of the present invention. However, it should be noted that many details listed in the specification are only for enabling the reader to have a thorough understanding of one or more aspects of the present invention, and these aspects of the present invention can be realized even without these specific details.

[0071] As Figure 1-2 shown, a composite functional material for accelerating aerobic sludge granulation, the composite functional material for accelerating aerobic sludge granulation is of a core - shell structure; in the core - shell structure, the core layer includes the following raw material components by mass percentage: sulfur source 30 - 50%, conductive medium 5 - 10%, pH buffer 0 - 5%; the shell layer includes the following raw material components by mass percentage: polylactic acid 10 - 50%, extracellular polymer - inducing enhancer A 0.6 - 1%, extracellular polymer - inducing enhancer B 0.002 - 0.005%, pyrite 15 - 35%; it also includes a chitin matrix, with a dosage of 50 - 65% of the mass of the core layer, and the chitin matrix serves as a raw material component for both the core layer and the shell layer.

[0072] The sulfur source described above is one or both of pyrite (FeS2, particle size ≤ 200 mesh, AR grade) and elemental sulfur (S0, particle size ≤ 200 mesh, AR grade).

[0073] The conductive medium described above is one or both of nano-carbon powder and graphite (C, particle size ≤ 200 mesh).

[0074] The pH buffer described above is nano-sodium silicate (Na2SiO3, particle size ≤ 200 mesh) or nano-calcium carbonate (CaCO3, particle size ≤ 200 mesh).

[0075] The extracellular polymer induction enhancer A described above is humus.

[0076] The extracellular polymer induction enhancer B described above is AI-2 signal molecule.

[0077] A preparation method of a composite functional material for accelerating aerobic sludge granulation includes the following steps:

[0078] S1 Chitin pretreatment: The chitin is washed with clean water, dried and then used. It is mechanically crushed and screened into nano-chitin powder with a particle size ≤ 200 mesh. Then the chitin powder is dissolved in 1% NaOH alkaline solution in small amounts and multiple times to remove protein, while stirring continuously. The stirring speed is maintained at 700 - 900 r / min, the temperature is controlled at 55 - 60 °C, and stirring is carried out for 2 - 3 h. The endogenous calcium carbonate is retained, and finally it is vacuum dried for use to obtain a chitin matrix.

[0079] S2 Core layer preparation and freeze molding: The sulfur source, chitin matrix, and conductive medium are mixed in a mass ratio of 5:4:1. At the same time, the content of endogenous calcium carbonate in the chitin matrix is detected. If the mass ratio of the endogenous calcium carbonate content in the chitin matrix to the sulfur source is less than 1:1, a pH buffer is added to make up the difference. After mixing, it is dispersed in a chitin solution of 4% NaOH / 6% urea, and ultrasonic homogenization is carried out for 30 - 60 min. After homogenization, it is preformed into spherical particles with a diameter of 1 - 2 mm by dropping liquid nitrogen, and then the spherical particles are vacuum freeze-dried at -50 °C for 24 h. After freezing, it is cross-linked with 1% glutaraldehyde vapor for 2 h, and the wet compressive strength > 5 N. After cross-linking, the thickness of the silica coating is made up to 1 - 2 μm to obtain core layer microspheres.

[0080] S3 Shell layer preparation and low-temperature foaming: The core layer microspheres and polylactic acid particles are melt-blended at a volume ratio of 1:1 at a temperature of 85 - 95 °C, and then supercritical CO2 foaming is carried out. The foaming pressure is 15 MPa and the temperature is 80 °C to make the polylactic acid particles foam, forming a porous shell layer with a bubble pore size of 50 - 200 mesh and a porosity > 70% to coat the core layer microspheres, obtaining particles with a diameter of 2.0 - 3.0 mm.

[0081] S4 functional loading and surface modification: the particles obtained in S3 were immersed in a mixed solution of humic acid and AI-2 in ethanol for 30-60 min, the coating thickness was controlled to be 5-10 μm by adjusting the concentration of the mixed solution, loaded through the pores of the shell layer, vacuum dried, and the surface was plasma etched at a power of 50 W for 6-10 min to adjust the surface roughness Ra to 1.8-2.8 μm, forming a micron-scale rough structure to obtain a preformed material;

[0082] S5 Density Control and Stability Enhancement: Spray the preformed material with a pyrite suspension with a particle size of ≤300 mesh to adjust the material density to 0.95-1.05g / cm 3 , and heat treated at 60°C for 1h under a nitrogen atmosphere to finally obtain a composite functional material with a particle size of 2-3mm.

[0083] The composite functional material is used in the treatment of low carbon-nitrogen ratio wastewater in municipal, industrial, surface water, groundwater and aquaculture water.

[0084] The application method of the composite functional material comprises the following steps:

[0085] S1: Material addition and reactor startup: Add composite functional material carrier according to 10-20% of the reactor volume, control the initial dissolved oxygen to 0.5-1.0 mg / L, pH = 6.5-7.5, HRT = 4-12h;

[0086] S2: Low dissolved oxygen graded control:

[0087] Stage I 0-7 days, sulfur autotrophic bacteria enrichment: DO = 0.5-1.0 mg / L, water intake 10-30%;

[0088] Stage II 8-14 days, granulation induction: increase DO = 1.0-2.0 mg / L, water intake 30-70%;

[0089] Stage III>14 days, stable operation: maintain DO=2.0-3.0mg / L, water inflow 70-100%;

[0090] S3: Long-term maintenance and material degradation: Aerobic granular sludge acclimation is completed and the process operates stably.

[0091] Example 1

[0092] A composite functional material for accelerating aerobic sludge granulation, wherein the composite functional material for accelerating aerobic sludge granulation has a core-shell structure; in the core-shell structure, the core layer comprises raw materials with the following mass percentages: elemental sulfur 40%, nano-carbon powder 5%, pH buffer 0%; the shell layer comprises raw materials with the following mass percentages: polylactic acid 30%, humic acid 0.8%, AI-2 signaling molecule 0.003%, pyrite 20%; it also includes a chitin matrix, and the dosage is 60% of the mass of the core layer, and the chitin matrix is used as a raw material component of both the core layer and the shell layer.

[0093] A preparation method of a composite functional material for accelerating aerobic sludge granulation, comprising the following steps:

[0094] S1 Chitin pretreatment: The chitin is washed with clean water, dried and then used. It is mechanically crushed and screened into nano-chitin powder with a particle size ≤ 200 mesh, and then the chitin powder is dissolved in 1% NaOH alkaline solution in small amounts and multiple times to remove protein. Stir while adding, and keep the stirring speed at 800 r / min, the temperature is controlled at 60 °C, stir for 2.5 h, retain the endogenous calcium carbonate, and finally vacuum dry for later use to obtain the chitin matrix;

[0095] S2 Core layer preparation and freeze molding: Mix the sulfur source, chitin matrix, and conductive medium according to a mass ratio of 5:4:1, and at the same time detect the content of endogenous calcium carbonate in the chitin matrix. In this example, the mass ratio of the endogenous calcium carbonate content in the chitin matrix to the sulfur source is greater than 1:1, and no pH buffer is added; after mixing, disperse it in a chitin solution of 4% NaOH / 6% urea, homogenize with ultrasonic waves for 60 min, and after homogenization, use liquid nitrogen to drop-freeze to form spherical particles with a diameter of 1.5 mm, and then vacuum freeze-dry the spherical particles at -50 °C for 24 h. After freezing, crosslink with 1% glutaraldehyde vapor for 2 h, and after crosslinking, coat with silica to a thickness of 1.5 μm to obtain core layer microspheres;

[0096] S3 Shell layer preparation and low-temperature foaming: Mix the core layer microspheres and polylactic acid particles according to a volume ratio of 1:1, melt and blend them at a temperature of 90 °C, and then use supercritical CO2 foaming. The foaming pressure is 15 MPa and the temperature is 80 °C to make the polylactic acid particles foam, forming a porous shell layer with a pore diameter of 100 mesh and a porosity > 70% to coat the core layer microspheres, obtaining particles with a diameter of 2.5 mm, and its pore channel scanning electron micrograph is as Figure 3 shown;

[0097] S4 Functional loading and surface modification: Immerse the particles obtained in S3 in an ethanol mixed solution of humic acid and AI-2 for 50 min, control the coating thickness to 10 μm by adjusting the concentration of the mixed solution, load through the pores in the shell layer, vacuum dry, and plasma etch the surface at a power of 50 W for 8 min to adjust the surface roughness Ra = 2 μm to form a micron-scale rough structure to obtain the preformed material;

[0098] S5 Density Regulation and Stability Enhancement: The preformed material is sprayed with a pyrite suspension to adjust the material density to 1.02 g / cm 3 , and heat-treated at 60 °C for 1 h in a nitrogen atmosphere to finally obtain a composite functional material with a particle size of 2 - 3 mm.

[0099] The composite functional material obtained in this example is applied to the advanced denitrification of municipal sewage (C / N = 2.5), with an effective volume of 100 m 3 , and a continuous-flow aerobic granular sludge reactor is used.

[0100] The application method includes the following steps:

[0101] S1: Material Feeding and Reactor Start-up: Add the composite functional material carrier at 20% of the reactor volume, control the initial dissolved oxygen to 1.0 mg / L, pH = 7, and HRT = 4 h;

[0102] S2: Low Dissolved Oxygen Hierarchical Control:

[0103] Stage I, days 0 - 7, sulfur autotrophic bacteria enrichment: DO = 1.0 mg / L, influent flow rate 30%;

[0104] Stage II, days 8 - 14, granulation induction: Increase DO = 1.5 mg / L, influent flow rate 60%;

[0105] Stage III, > 14 days, stable operation: Maintain DO = 2.5 mg / L, influent flow rate 70%;

[0106] S3: Long-term Maintenance and Material Degradation: After the domestication of aerobic granular sludge is completed, the process operates stably.

[0107] After applying the functional material of this example to the advanced denitrification of municipal sewage, the operation effect is as follows:

[0108] Granulation process: Sludge with a particle size of 2.0 mm is formed in 14 days, the sedimentation rate is 38 m / h, and SVI 30 = 32 mL / g;

[0109] Denitrification performance: TN removal rate is 93.5%, sulfate concentration is 38 mg / L, and sulfur utilization rate is 87%;

[0110] Material degradation: The mass loss rate is 12% after 6 months of operation, and the complete degradation period is 9 months.

[0111] Example 2

[0112] A composite functional material for accelerating aerobic sludge granulation, wherein the composite functional material for accelerating aerobic sludge granulation has a core-shell structure; in the core-shell structure, the core layer comprises raw materials with the following mass percentages: 50% of pyrite, 5% of graphite, and 5% of nano calcium carbonate; the shell layer comprises raw materials with the following mass percentages: 10% of polylactic acid, 1% of humic acid, 0.005% of AI-2 signal molecule, and 35% of pyrite; it also includes a chitin matrix, with a dosage of 60% of the mass of the core layer, and the chitin matrix serves as a raw material component of both the core layer and the shell layer.

[0113] A preparation method of the composite functional material for accelerating aerobic sludge granulation, comprising the following steps:

[0114] S1 Chitin pretreatment: The chitin is washed with clean water, dried, and then used. It is mechanically crushed and screened into nano chitin powder with a particle size ≤ 200 mesh. Then, the chitin powder is dissolved in 1% NaOH alkaline solution in small amounts and multiple times to remove protein. Stir while adding, keep the stirring speed at 900 r / min, control the temperature at 58 °C, stir for 3 h, retain the endogenous calcium carbonate, and finally vacuum dry for later use to obtain the chitin matrix.

[0115] S2 Core layer preparation and freeze molding: Mix the sulfur source, chitin matrix, and conductive medium according to a mass ratio of 5:4:1. At the same time, detect the endogenous calcium carbonate content of the chitin matrix. In this embodiment, the mass ratio of the endogenous calcium carbonate content of the chitin matrix to the sulfur source is less than 1:1, so nano calcium carbonate is added to make up the difference. After mixing, disperse it in a chitin solution of 4% NaOH / 6% urea, homogenize with ultrasonic waves for 30 min. After good homogenization, use liquid nitrogen to drip-freeze and pre-form spherical particles with a diameter of 2 mm, and then vacuum freeze-dry the spherical particles at -50 °C for 24 h. After freezing, crosslink with 1% glutaraldehyde vapor for 2 h, and then coat with silica to a thickness of 2 μm to obtain core layer microspheres.

[0116] S3 Shell layer preparation and low-temperature foaming: Mix the core layer microspheres and polylactic acid particles according to a volume ratio of 1:1, melt-blend them at a temperature of 85 °C, and then use supercritical CO2 foaming. The foaming pressure is 15 MPa and the temperature is 80 °C to make the polylactic acid particles foam, forming a porous shell layer with a bubble pore size of 150 mesh and a porosity > 70% to coat the core layer microspheres, obtaining particles with a diameter of 2 mm.

[0117] S4 Functional loading and surface modification: Immerse the particles obtained in S3 in an ethanol mixed solution of humic acid and AI-2 for 30 min, control the coating thickness to 5 μm by adjusting the concentration of the mixed solution, load through the pores of the shell layer, vacuum dry, and plasma etch the surface at a power of 50 W for 10 min to adjust the surface roughness Ra = 2.8 μm to form a micron-level rough structure, obtaining a preformed material.

[0118] S5 Density Regulation and Stability Enhancement: The preformed material is sprayed with a pyrite suspension to adjust the material density to 1.05 g / cm 3 , and heat-treated at 60 °C for 1 h under a nitrogen atmosphere to finally obtain a composite functional material with a particle size of 2-3 mm.

[0119] The composite functional material obtained in this example is applied to the treatment of industrial printing and dyeing wastewater (C / N = 1.2, containing 100 mg / L of nitrate nitrogen), and a continuous flow aerobic granular sludge reactor with an effective volume of 1000 m 3 .

[0120] The application method includes the following steps:

[0121] S1: Material Feeding and Reactor Startup: Add the composite functional material carrier at 15% of the reactor volume, control the initial dissolved oxygen to 0.5 mg / L, pH = 7.5, and HRT = 8 h.

[0122] S2: Low Dissolved Oxygen Gradient Control:

[0123] Stage I (0-7 days), Sulfur Autotrophic Bacteria Enrichment: DO = 0.8 mg / L, influent flow rate 10%.

[0124] Stage II (8-14 days), Granulation Induction: Increase DO = 2 mg / L, influent flow rate 30%,

[0125] Stage III (>14 days), Stable Operation: Maintain DO = 3 mg / L, influent flow rate 100%;

[0126] S3: Long-Term Maintenance and Material Degradation: After the aerobic granular sludge is domesticated, the process operates stably.

[0127] After applying this example to the treatment of process polluted wastewater, the operation effect is as follows:

[0128] Sulfur Release Rate: 0.12 mg S / (g·h);

[0129] Shock Resistance Load: When the influent TN fluctuates (50-150 mg / L), the TN removal rate remains stable > 85%;

[0130] Granulation Time: Sludge with a particle size of 2.5 mm and a density of 1.04 g / cm is formed in 16 days 3 ;

[0131] Denitrification Performance: TN Removal Rate 91.8%, Sulfate Concentration 45 mg / L, Sulfur Utilization Rate 83%;

[0132] Material Degradation: The mass loss rate is 18% after 6 months of operation, and the complete degradation cycle is 12 months.

[0133] Example 3

[0134] A composite functional material for accelerating aerobic sludge granulation, and the composite functional material for accelerating aerobic sludge granulation has a core-shell structure; in the core-shell structure, the core layer comprises raw materials with the following mass percentages: 30% sulfur source, 10% nano-carbon powder, 0% pH buffer; the shell layer comprises raw materials with the following mass percentages: 50% polylactic acid, 0.6% humic acid, 0.002% AI-2 signaling molecule, 15% pyrite; it also includes a chitin matrix, and the dosage is 65% of the mass of the core layer, and the chitin matrix serves as a raw material component of both the core layer and the shell layer at the same time.

[0135] The sulfur source is elemental sulfur and pyrite, and the dosages of elemental sulfur and pyrite are both 15%.

[0136] The conductive medium is nano-carbon powder and graphite, and the dosages of nano-carbon powder and graphite are both 5%.

[0137] A preparation method of a composite functional material for accelerating aerobic sludge granulation, comprising the following steps:

[0138] S1 Chitin pretreatment: The chitin is washed with clean water, dried and then used. It is mechanically crushed and screened into nano-chitin powder with a particle size ≤ 200 mesh, and then the chitin powder is dissolved in 1% NaOH lye in small amounts and multiple times to remove protein. Stir while adding, and keep the stirring speed at 700 r / min, control the temperature at 55 °C, stir for 2 h, retain endogenous calcium carbonate, and finally vacuum dry for use to obtain a chitin matrix.

[0139] S2 Core layer preparation and freeze molding: The sulfur source, chitin matrix, and conductive medium are mixed in a mass ratio of 5:4:1. At the same time, the content of endogenous calcium carbonate in the chitin matrix is detected. In this embodiment, the mass ratio of the endogenous calcium carbonate content in the chitin matrix to the sulfur source is greater than 1:1, and no pH buffer is added; after mixing, it is dispersed in a 4% NaOH / 6% urea chitin solution, ultrasonic homogenization is carried out for 50 min, and after homogenization, it is preformed into spherical particles with a diameter of 1 mm by drop-freezing with liquid nitrogen, and then the spherical particles are vacuum freeze-dried at -50 °C for 24 h. After freezing, it is cross-linked with 1% glutaraldehyde vapor for 2 h, and after cross-linking, it is coated with silica to a thickness of 1 μm to obtain core layer microspheres.

[0140] S3 Shell layer preparation and low-temperature foaming: The core layer microspheres and polylactic acid particles are melt-blended at a volume ratio of 1:1 at a temperature of 95 °C, and then supercritical CO2 foaming is carried out. The foaming pressure is 15 MPa and the temperature is 80 °C to make the polylactic acid particles foam, forming a porous shell layer with a bubble pore size of 80 mesh and a porosity > 70% to coat the core layer microspheres, obtaining particles with a diameter of 3 mm.

[0141] S4 Functional Load and Surface Modification: Immerse the particles obtained in S3 in an ethanol mixed solution of humic acid and AI-2 for 60 min. Control the coating thickness to be 8 μm by adjusting the concentration of the mixed solution. Through loading within the pores of the shell layer and vacuum drying, perform plasma etching on the surface at a power of 50 W for 6 min, and adjust the surface roughness Ra = 1.8 μm to form a micron-scale rough structure, obtaining a preformed material;

[0142] S5 Density Regulation and Stability Enhancement: Spray a pyrite suspension on the preformed material to adjust the material density to 0.95 g / cm 3 , and perform heat treatment at 60 °C for 1 h in a nitrogen atmosphere to finally obtain a composite functional material with a particle size of 2 - 3 mm.

[0143] The release rate of the composite functional material obtained in this example is 1.8 mg S / (g·h).

[0144] Apply the composite functional material obtained in this example to the treatment process of aquaculture wastewater (C / N = 1.5), using a traditional SBR reactor with an effective volume of 2000 m 3 .

[0145] The application method includes the following steps:

[0146] S1: Material Feeding and Reactor Start-up: Add the composite functional material carrier according to 10% of the reactor volume, control the initial dissolved oxygen to be 0.8 mg / L, pH = 6.5, and HRT = 12 h;

[0147] S2: Low Dissolved Oxygen Hierarchical Control:

[0148] Phase I, days 0 - 7, enrichment of sulfur autotrophic bacteria: DO = 0.5 mg / L, influent volume 15%;

[0149] Phase II, days 8 - 14, granulation induction: increase DO = 1.2 mg / L, influent volume 70%;

[0150] Phase III, > 14 days, stable operation: maintain DO = 2 mg / L, influent volume 80%;

[0151] S3: Long-term Maintenance and Material Degradation: After the acclimation of aerobic granular sludge is completed, the process operates stably.

[0152] After applying this example to the treatment of aquaculture wastewater, the operation effect is as follows:

[0153] Sulfur slow release rate: 0.08 mg S / (g·h);

[0154] Long-term stability: Continuously operate for 180 days, the particles do not disintegrate, and the EPS content > 160 mg / g VSS;

[0155] Denitrification performance: TN removal rate is 92.3%, COD is simultaneously removed by 88%, and sulfate concentration is 28 mg / L;

[0156] Material degradation: mass loss rate is 8% after 6 months of operation, and the complete degradation cycle is 6 months.

[0157] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.

Claims

1. A composite functional material for accelerating aerobic sludge granulation, characterized in that: The composite functional material described is of a core-shell structure; in the core-shell structure, the core layer comprises raw materials with the following mass percentages: 30-50% of a sulfur source, 5-10% of a conductive medium, and 0-5% of a pH buffer; the shell layer comprises raw materials with the following mass percentages: 10-50% of polylactic acid, 0.6-1% of extracellular polymer induction enhancer A, 0.002-0.005% of extracellular polymer induction enhancer B, and 15-35% of pyrite; it also includes a chitin matrix, with a dosage of 50-60% of the mass of the core layer, and the chitin matrix serves as a raw material component for both the core layer and the shell layer.

2. The composite functional material for accelerating aerobic sludge granulation according to claim 1, characterized in that: The sulfur source described is one or both of pyrite and elemental sulfur.

3. The composite functional material for accelerating aerobic sludge granulation according to claim 1, wherein: The conductive medium described is one or both of nano carbon powder and graphite.

4. The composite functional material for accelerating aerobic sludge granulation according to claim 1, characterized in that: The pH buffer described is sodium silicate nanometer or calcium carbonate nanometer.

5. The composite functional material for accelerating aerobic sludge granulation according to claim 1, wherein: The extracellular polymer induction enhancer A described is humus.

6. The composite functional material for accelerating aerobic sludge granulation according to claim 1, wherein: The extracellular polymer induction enhancer B described is AI-2 signaling molecule.

7. The preparation method of the composite functional material for accelerating aerobic sludge granulation according to claim 1, characterized in that, It includes the following steps: S1 Chitin pretreatment: The chitin is washed clean with clear water, dried, and then mechanically broken and screened into nano-chitin powder. Then, the chitin powder is dissolved in 1% NaOH alkaline solution in small amounts and multiple times for deproteinization. Stir while adding, and keep the stirring speed at 700-900 r / min, the temperature is controlled at 55-60 °C, stir for 2-3 h, retain the endogenous calcium carbonate, and finally vacuum dry for use to obtain the chitin matrix. S2 Core layer preparation and freeze forming: The sulfur source, chitin matrix, and conductive medium are mixed in a mass ratio of 5:4:

1. At the same time, detect the content of endogenous calcium carbonate in the chitin matrix, add a pH buffer according to the content of endogenous calcium carbonate. After mixing, disperse it in the chitin solution, and homogenize with ultrasonic waves for 30-60 min. After good homogenization, use liquid nitrogen to drop-freeze to form spherical particles with a diameter of 1-2 mm, and then vacuum freeze-dry the spherical particles at -50 °C for 24 h. After freezing, crosslink with 1% glutaraldehyde vapor for 2 h, and after crosslinking, coat with silicon dioxide to a thickness of 1-2 μm to obtain core layer microspheres. S3 Shell layer preparation and low-temperature foaming: The core layer microspheres and polylactic acid particles are melt-blended at a volume ratio of 1:1 at a temperature of 85-95 °C, and then foamed with supercritical CO2. The foaming pressure is 15 MPa and the temperature is 80 °C, so that the polylactic acid particles foam and coat the core layer to form particles. S4 Functional loading and surface modification: Immerse the particles obtained in S3 in an ethanol mixed solution of humic acid and AI-2 for 30-60 min, control the coating thickness to 5-10 μm by adjusting the concentration of the mixed solution, load through the pores in the shell layer, vacuum dry, and plasma etch the surface at a power of 50 W for 6-10 min to adjust the surface roughness Ra = 1.8-2.8 μm to form a micron-scale rough structure to obtain a preformed material. S5 Density Regulation and Stability Enhancement: Adjust the density of the preformed material to 0.95 - 1.05 g / cm by spraying a pyrite suspension 3 , and heat-treat it under a nitrogen atmosphere to finally obtain a particle-size composite functional material.

8. Use of the composite functional material for accelerating aerobic sludge granulation according to claim 1, characterized in that: In S2, if the mass ratio of the content of endogenous calcium carbonate in the chitin matrix to the sulfur source is less than 1:1, add a pH buffer to make up.

9. Use of the composite functional material for accelerating aerobic sludge granulation according to claim 1, characterized in that: The application of the composite functional material in the treatment of low-carbon and nitrogen ratio wastewater in municipal, industrial, surface water, groundwater, and aquaculture water.

10. Use of the composite functional material for accelerating aerobic sludge granulation according to claim 9, characterized in that, The application method of the composite functional material includes the following steps: S1: Material dosing and reactor startup: Add the composite functional material carrier at 10 - 20% of the reactor volume, control the initial dissolved oxygen at 0.5 - 1.0 mg / L, pH = 6.5 - 7.5, and HRT = 4 - 12 h; S2: Low dissolved oxygen hierarchical control: Phase I, days 0 - 7, enrichment of sulfur autotrophic bacteria: DO = 0.5 - 1.0 mg / L, influent flow rate 10 - 30%; Phase II, days 8 - 14, granulation induction: Increase DO = 1.0 - 2.0 mg / L, influent flow rate 30 - 70%; Phase III, > 14 days, stable operation: Maintain DO = 2.0 - 3.0 mg / L, influent flow rate 70 - 100%; S3: Long-term maintenance and material degradation: After the acclimation of aerobic granular sludge, the process operates stably.

Citation Information

Patent Citations

  • Porous material based on beta-chitin as well as preparation method and application of porous material

    CN117624712A

  • Composite filler for sulfur autotrophic denitrification biological filter as well as preparation method and application of composite filler

    CN118108346A

  • Method for preparing ferrous sulfide-based autotrophic denitrification filler by mechanochemical method and application of ferrous sulfide-based autotrophic denitrification filler

    CN118878074A

  • Method for intensively inducing aerobic sludge granulation by means of humic acid

    CN106430553A

  • Method for using signal molecules for accelerating repair of disintegrated aerobic granular sludge

    CN109987698A